COST OF ILLNESS OF INPATIENT PEDIATRIC MENINGITIS PATIENTS HOSPITALIZED IN YOGYAKARTA - Ingenida Hadning; Dwi Endarti; Tri Murti Andayani; Rina Triasih (Jurnal Farmasi Sains dan Praktis, 2020)
This research to determine the average cost of illness of inpatient pediatric meningitis patients hospitalized in the hospitals in Yogyakarta. It was a pharmacoeconomic study using the cost of illness method. The calculation of the cost in the care of inpatient pediatric meningitis patients according to a societal perspective was conducted observatively with a cross sectional design. Cost of illness analysis included calculating the costs of direct medical, direct non-medical, and indirect cost. Data were collected from a type-A public hospital and a type-B privatehospital in Yogyakarta by taking medical records, detailed data on meningitis patient care costs, and interviews using questionnaires with caregivers. Analysis of cost of illness calculations applied descriptive analysis methods. In this study, 11 inpatient pediatric meningitis patients were obtained. The average cost of illness for the treatment of inpatient pediatric meningitis patients was IDR 26,224,586±12,814,789, consisting of the average direct medical cost of IDR 23,831,813±12,222,885 (90.88%), the average direct non-medical cost of IDR 1,787,955±832,353 (6.82%), and the average indirect cost of IDR 604,818±337,389 (2.31%). Components of direct medical cost with the largest percentage were drugs and medical supplies (26.46%); while the largest direct non-medical cost were the expenditure of additional needs for the patient's family (72.18%). The indirect cost component came from the reduction of the patient's parents' income while the patient is hospitalized.